A description of the acute cardiovascular responses to isokinetic resistance at three different speeds - Kleiner, D. M.; Blessing, D. L.; Mitchell, J. W.; Davis, W. R. (The Journal of Strength and Conditioning Research, 1999)
Isokinetics remains a popular form of resistance in the clinical setting for orthopedic rehabilitation; however, little is known about its effect on the cardiovascular system. The present study was designed to describe the acute cardiovascular responses to isokinetic exercises at 3 different speeds. Heart rate, intra-arterial systolic and diastolic blood pressures, and the rate-pressure product were directly and continuously recorded during all exercises. Peak heart rates and the rate-pressure product increased with increases in isokinetic velocity. Systolic and diastolic blood pressures decreased as the isokinetic velocity increased. The differences in cardiovascular values among the isokinetic speeds were not of great magnitude but did increase substantially from the values obtained during rest. Both ratings of perceived exertion and torque values increased as the isokinetic velocity decreased. These data show that cardiovascular stress is increased during isokinetic exercises and that responses may differ among the various speeds.